Effects of Neoadjuvant Chemotherapy on Rates of Depression in Muscle Invasive Bladder Cancer - Matthew DeSanto; Frank H. Annie; Stacie Deslich; Thomas Cato; Clayton Davis; Nathan Hale (Journal of Urologic Oncology)
Purpose The objective of this large retrospective cohort study is to better understand the relationship of bladder cancer and depression incidence, specifically relating to the incorporation of neoadjuvant chemotherapy (NCT) in treatment plans. Materials and Methods This is a large retrospective cohort study utilizing a formulated dataset from the TriNetX Research Network Database. ICD-10 (International Statistical Classification of Diseases, 10th revision) codes related to bladder cancer and depression diagnoses and treatments were implemented to identify patients of interest. Propensity score matching was implemented for various demographic factors and comorbidities. The patient population was limited to stage T2 bladder cancer, and NCT was defined as receival within 90 days prior to cystectomy (CYS). The primary outcome was denoted as depressive episode diagnosis within 3 months of CYS. Secondary outcomes of hospitalizations, mortality, and suicide attempts within 3 months of CYS were analyzed. Results In total, 4,630 patients were included after propensity score matching, yielding 2,315 patients per group. All patients had T2 disease and underwent CYS. In the NCT cohort, 243 patients (10.5%) acquired a diagnosis of depression within 3 months from CYS compared to 144 patients (6.2%) who received no NCT (95% confidence interval [CI], 0.027– 0.059; p<0.001). Odds ratio was 1.768 (95% CI, 1.426–2.192) when comparing cohorts with and without NCT. There was no statistical difference in mortality (95% CI, -0.012 to 0.014; p=0.844) or inpatient hospitalizations (95% CI, -0.046 to 0.009; p=0.191) within 3 months. There was a statistically significant increase in suicide attempts in the NCT group within 3 months (95% CI, 0.002–0.007; p=0.002). Conclusions Bladder cancer can induce significant patient morbidity with ensuing depression. Our retrospective cohort study demonstrates NCT correlates to increased incidence of depression as well as suicidal attempts. Assiduous attention needs to be directed towards mental health counseling and treatment for oncologic patients.